Iron maltol-oxalic acid eutectic crystal and preparation method thereof
By combining maltol iron and oxalic acid, the suspension stirring method is used to form maltol iron-oxalic acid eutectics, which solves the problems of stability and efficacy of maltol iron preparations in large-scale production, achieves higher stability and thermal stability, extends the shelf life and reduces the risks of production and quality control.
Patent Information
- Application Number
- CN202411807797.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-09
AI Technical Summary
In large-scale production of existing maltol iron preparations, there is a risk that stable crystal forms are difficult to obtain quickly and efficiently and mix crystal forms I and II, and there are adverse gastrointestinal reactions, and there is a lack of a stable solid form to improve drug properties.
The suspension stirring method is used to combine the maltol iron and oxalic acid to form maltol iron-oxalic acid eutectics, and the eutectics are formed through hydrogen bond interaction to improve stability and thermal stability.
The stability and thermal stability of maltol iron-oxalic acid eutectics are achieved, the shelf life of the preparation is extended, the risks of drug efficacy decline and quality problems are reduced, and processability and adaptability are improved.
Smart Images

Figure CN119638662A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of medical technology and relates to a drug cocrystal, and specifically relates to a maltol iron-oxalic acid cocrystal and a preparation method thereof. Background Art
[0002] A drug cocrystal refers to a new type of crystal structure formed by the assembly of the active ingredient of a drug and a suitable cocrystal ligand in a certain proportion under the action of hydrogen bonding, π-π stacking, van der Waals force or other non-covalent bonds. It does not change the chemical structure of the original drug, but improves the physicochemical properties and efficacy of the drug itself by physical means, such as improving solubility, enhancing stability and improving bioavailability.
[0003] Ferric maltol is a new type of non-salt complex with stable chemical properties formed by iron and maltol. It has properties similar to phenol and is a reddish brown crystalline solid. Its chemical structure is as follows:
[0004]
[0005] Maltol iron can provide iron, supplement the nutrients needed by the body, and prevent or treat iron deficiency anemia. Maltol iron has a unique absorption mechanism and has obvious advantages over similar iron supplements. Maltol iron capsules, developed by Shield Therapeutics in the UK, were approved by the European Medicines Agency (EMA) and the US Food and Drug Administration (FDA) in 2016 and 2019 for the treatment of iron deficiency in adults (with or without anemia symptoms). For patients who are intolerant to existing oral iron preparations or have poor treatment effects, maltol iron capsules are an ideal alternative. At present, there are reports of a variety of maltol iron crystal forms. Patent application WO2016066555A1 discloses four polymorphic forms of maltol iron (ie, crystal forms I, II, III, and IV), and patent US20210139518A1 discloses a new crystal form of maltol iron (ie, crystal form V). However, the existing methods cannot quickly and efficiently obtain a stable crystal form of ferric maltol, and there is a risk of mixing crystal form I and crystal form II, which brings certain challenges to large-scale production. It has also been reported that the main adverse reactions of ferric maltol include: gastrointestinal inflammation, gastrointestinal flatulence, constipation, diarrhea, etc. (Khoury A, Pagan KA, Farland MZ. Ferric maltol: A new oral iron formulation for the treatment of iron deficiency in adults. Ann Pharmacother. 2021, 55 (2): 222-229).
[0006] There is no report on maltol iron eutectic so far, so developing a new solid form of maltol iron is of great significance to improve its drugability and clinical application. Summary of the invention
[0007] The purpose of the present invention is to provide a maltol iron-oxalic acid eutectic formed by combining maltol iron and a medicinal small molecule auxiliary material oxalic acid and a preparation method thereof.
[0008] The objective of the present invention is achieved through the following technical solutions:
[0009] The invention discloses a maltol iron-oxalic acid eutectic, which takes maltol iron as a pharmaceutical active ingredient and oxalic acid as a eutectic ligand and is formed by a suspension stirring method.
[0010] In the X-ray powder diffraction pattern measured using Cu-Kα radiation, the maltol iron-oxalic acid cocrystal has characteristic diffraction peaks at diffraction angles 2θ of approximately 14.7±0.2°, 17.0±0.2°, 17.6±0.2°, 24.8±0.2°, 26.6±0.2°, and 26.9±0.2°, and the 2θ angle of the characteristic peak with a relative intensity of 100% is 26.6±0.2°.
[0011] Preferably, in the X-ray powder diffraction pattern measured using Cu-Kα radiation, the maltol iron-oxalic acid cocrystal has characteristic diffraction peaks at diffraction angles 2θ of approximately 14.7±0.2°, 15.9±0.2°, 17.0±0.2°, 17.6±0.2°, 22.0±0.2°, 24.8±0.2°, 25.7±0.2°, 26.6±0.2°, and 26.9±0.2°.
[0012] More preferably, the maltol iron-oxalic acid eutectic has Figure 1 or Figure 5 The X-ray powder diffraction pattern is shown.
[0013] The infrared spectrum obtained by mixing and pressing the maltol iron-oxalic acid eutectic with potassium bromide is 1074.41 cm -1 、1205.56cm -1 、1277.91cm -1 、1353.16cm -1 、1384.55cm -1 、1399.84cm -1 、1495.65cm -1 、1560.58cm -1 、1606.82cm -1 、1664.18cm -1 、3256.93cm -1There is an absorption peak at; in the differential scanning calorimetry (DSC) spectrum, the maltol iron-oxalic acid eutectic has a single endothermic melting peak at 310.93°C.
[0014] The ferric maltol-oxalic acid eutectic is a eutectic formed by the interaction of ferric maltol and oxalic acid through hydrogen bonds.
[0015] The molar ratio of maltol iron to oxalic acid in the maltol iron-oxalic acid eutectic is 1:1 to 1:2, preferably 1:1.
[0016] Another object of the present invention is to provide a method for preparing the maltol iron-oxalic acid eutectic, which adopts a suspension stirring method and comprises the following steps: adding maltol iron and oxalic acid to an organic solvent to form a suspension, stirring the reaction, filtering, and vacuum drying to obtain the maltol iron-oxalic acid eutectic.
[0017] The ratio of the amount of the maltol iron to the amount of oxalic acid is 1:1 to 1:2, preferably 1:1.
[0018] The organic solvent is ethanol, methanol, acetonitrile, ethyl acetate or a mixed solvent of at least two of the above organic solvents, preferably ethanol.
[0019] The dosage ratio of the ferric maltol to the organic solvent is 2:1 to 500:1 mg / mL, preferably 50:1 to 200:1 mg / mL.
[0020] The reaction temperature is 25-45°C, preferably 15-30°C, and most preferably room temperature (25°C).
[0021] The reaction time is 3 to 7 days, preferably 5 to 6 days.
[0022] The rotation speed of the stirring reaction is 50 to 1000 rpm, preferably 200 to 400 rpm.
[0023] Another object of the present invention is to provide a pharmaceutical composition, which comprises the maltol ferric-oxalic acid cocrystal and a pharmaceutically acceptable carrier.
[0024] Beneficial effects of the present invention:
[0025] (1) The PXRD, DSC and IR spectra of the ferric maltol-oxalic acid eutectic of the present invention are different from those of ferric maltol crystals, oxalic acid crystals and the physical mixture of ferric maltol and oxalic acid, and the eutectic is a new solid state completely different from the existing ferric maltol and oxalic acid;
[0026] (2) The maltol iron-oxalic acid eutectic of the present invention will not undergo crystal transformation under accelerated conditions (40°C, 75% RH) for at least 60 days, has good stability, can extend the shelf life of the eutectic preparation, reduce the decline in efficacy and quality problems caused by crystal transformation, and reduce the risks of production and quality control.
[0027] (3) Compared with ferric maltol, the ferric maltol-oxalic acid eutectic has a higher melting point, indicating that the eutectic system has higher thermal stability and is less likely to decompose or undergo phase change under high temperature conditions such as spray drying and hot melt extrusion in the heat treatment process in the pharmaceutical industry, making it have better processability and adaptability; at the same time, it can improve the stability of the eutectic system and the consistency of the product.
[0028] (4) The present invention introduces oxalic acid as a eutectic ligand. Compared with ferric maltol, the solubility of ferric maltol-oxalic acid eutectic in water is relatively lower. Low-solubility eutectics usually dissolve more slowly, which provides a new solution for the design of sustained-release and long-acting drug release systems, thereby avoiding the peak drug concentration in a short period of time, reducing the toxic and side effects of ferric maltol and improving medication compliance.
[0029] (5) The preparation method of maltol iron oxalate eutectic of the present invention is simple, low-cost, easy to control, and conducive to industrial production.
[0030] (6) Compared with amorphous solid dispersion technology, which usually requires a polymer carrier that is several times the amount of the drug to fully disperse the drug, the maltol iron-oxalic acid eutectic of the present invention has a high drug loading capacity, has a significant drug loading advantage, and has better stability; compared with nanotechnology, the maltol iron-oxalic acid eutectic of the present invention is easier to industrialize and its quality is easier to control. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is the PXRD pattern of the maltol iron-oxalic acid eutectic prepared in Example 1.
[0032] Figure 2 This is a PXRD comparison chart of the ferric maltol-oxalic acid eutectic prepared in Example 1 and ferric maltol and oxalic acid.
[0033] Figure 3 This is a DSC comparison chart of the ferric maltol-oxalic acid eutectic, ferric maltol and oxalic acid prepared in Example 1.
[0034] Figure 4 This is a comparison chart of infrared spectra of ferric maltol, oxalic acid, a physical mixture of ferric maltol and oxalic acid, and a eutectic of ferric maltol and oxalic acid.
[0035] Figure 5 This is the PXRD pattern of the maltol iron-oxalic acid eutectic prepared in Example 2.
[0036] Figure 6 This is a PXRD comparison chart of the maltol iron-oxalic acid eutectic in Example 1 placed under accelerated conditions (40°C, 75% RH) for 60 days and 0 day.
[0037] Figure 7 This is the PXRD pattern of the product prepared by slurrying maltol iron and L-cysteine in acetone, ethanol, acetonitrile or ethyl acetate in Comparative Example 1.
[0038] Figure 8 This is the PXRD pattern of the product prepared by slurrying maltol iron and nicotinamide in acetone, ethanol, acetonitrile or ethyl acetate in Comparative Example 2. DETAILED DESCRIPTION
[0039] The maltol iron used in preparing the maltol iron-oxalic acid eutectic is maltol iron crystal form II; the maltol iron (crystal) used for comparison with the maltol iron-oxalic acid eutectic is maltol iron crystal form II.
[0040] Example 1
[0041] Preparation of maltol iron-oxalic acid eutectic:
[0042] According to the molar ratio of maltol iron to oxalic acid of 1:1, 30 mg of maltol iron and 6.26 mg of oxalic acid were weighed, 0.5 mL of anhydrous ethanol was added, and the mixture was slurried with magnetic stirring (speed 400 rpm) at room temperature (25°C) for 6 days, filtered, and the filter cake was vacuum dried at 40°C for 24 hours to obtain a solid product, which was the maltol iron-oxalic acid eutectic.
[0043] The product was characterized by X-ray powder diffraction (PXRD) using Cu-Kα radiation. Figure 1 shown.
[0044] The PXRD patterns of maltol iron-oxalic acid eutectic were compared with those of maltol iron and oxalic acid. Figure 2 As shown in Table 1, the PXRD pattern of the cocrystal is significantly different from that of ferric maltol and oxalic acid. Further comparison of the characteristic peaks of the three is shown in Table 1. The cocrystal has characteristic diffraction peaks at diffraction angles 2θ of approximately 14.71°, 17.03°, 17.57°, 24.82°, 26.58°, and 26.94°, which are significantly different from those of ferric maltol and oxalic acid.
[0045] Table 1. Comparison of PXRD characteristic diffraction peak positions of maltol iron-oxalic acid eutectic and oxalic acid and maltol iron
[0046]
[0047]
[0048] The thermal properties of the ferric maltol-oxalic acid eutectic, ferric maltol and oxalic acid prepared in this example were analyzed by differential scanning calorimetry (DSC). The method is as follows: take about 3 mg of sample, use nitrogen as protective gas, nitrogen flow rate 100 mL / min, heating rate 10°C / min, temperature range 40-400°C. Figure 3 It can be seen that the thermal behaviors of ferric maltol, oxalic acid and ferric maltol-oxalic acid eutectic are significantly different. The melting point of ferric maltol is 288.87°C, the melting point of oxalic acid is 198.02°C, and the melting point of ferric maltol-oxalic acid eutectic is 310.93°C. The higher melting point indicates that the ferric maltol-oxalic acid eutectic has better thermal stability and is not easy to decompose or undergo phase change under high temperature conditions such as spray drying and hot melt extrusion, so that it often has better processability and adaptability, while improving the stability and consistency of the product.
[0049] Comparison of infrared spectra of maltol iron-oxalic acid eutectic: The maltol iron-oxalic acid eutectic, maltol iron and oxalic acid, and maltol iron-oxalic acid physical mixture (the molar ratio of oxalic acid in maltol iron is 1:1) prepared in this example were pressed into thin sheets with KBr, and infrared spectrometer was used to analyze the eutectic at 4000-400 cm -1 The infrared absorption spectra were compared and the results were as follows: Figure 4 shown.
[0050] from Figure 4 It can be seen that the maltol iron-oxalic acid eutectic is at 1074.41 cm -1 、1205.56cm -1 、1277.91cm -1 、1353.16cm -1 、1384.55cm -1 、1399.84cm -1 、1495.65cm -1 、1560.58cm -1 、1606.82cm -1 、1664.18cm -1 、3256.93cm -1 There are characteristic peaks near 3256.93cm, which are significantly different from maltol iron and oxalic acid. -1 In the stretching vibration region of OH in oxalic acid, 1664.18 cm -1 In the stretching vibration region of C=O in oxalic acid, 1606.82cm -1 In the stretching vibration region of C=O in maltol iron, 1495.65cm -1 、1560.58cm -1It is in the stretching vibration region of C=C in maltol iron. The spectral differences between maltol iron-oxalic acid eutectic and maltol iron and oxalic acid in these regions indicate that the OH and C=O functional groups in the eutectic have changed relative to the two components, and it is speculated that the maltol iron-oxalic acid eutectic is formed by hydrogen bonding.
[0051] Example 2
[0052] Preparation of maltol iron-oxalic acid eutectic:
[0053] According to the molar ratio of maltol iron to oxalic acid of 1:1, 30 mg of maltol iron and 6.26 mg of oxalic acid were weighed, 0.5 mL of ethanol was added, and the mixture was slurried for 6 days under magnetic stirring (speed 200 rpm) at room temperature (25°C), filtered, and the filter cake was vacuum dried at 40°C for 24 hours. The solid product obtained was maltol iron-oxalic acid eutectic. The product was characterized by an X-ray powder diffraction (PXRD) instrument, using Cu-Kα radiation, and the PXRD spectrum was as follows: Figure 5 shown.
[0054] Example 3
[0055] Study on the stability of maltol iron-oxalic acid eutectic
[0056] The maltol iron-oxalic acid eutectic prepared in Example 1 was placed in a constant temperature and humidity chamber under accelerated conditions (40° C., 75% RH), and samples were taken on the 60th day. The samples were characterized using an X-ray powder diffraction (PXRD) instrument, and the results are as follows: Figure 6 As shown. Figure 6 It can be seen that the ferric maltol-oxalic acid eutectic does not undergo crystal transformation under accelerated conditions for at least 60 days.
[0057] Table 2. Comparison of PXRD characteristic diffraction peak positions of maltol iron-oxalic acid eutectic at 40°C and 75% RH for 0 and 60 days
[0058]
[0059]
[0060] Example 4
[0061] Solubility determination
[0062] Test solution: 5 mL of water was measured and placed in a vial, and an excess of ferric maltol or ferric maltol-oxalic acid eutectic (Example 1) was added. The vial was sealed and placed under magnetic stirring at 25°C to reach equilibrium (24 h), and then filtered through a 0.22 μm microporous filter membrane to obtain the test solution.
[0063] Reference solution: Take 5.0 mg of maltol iron reference, accurately weigh it, put it in a 100 mL volumetric flask, add water to dissolve and dilute to the scale, shake well, filter through a 0.22 μm microporous filter membrane, and obtain the solution.
[0064] Determination of maltol iron content: Determine by ultraviolet spectrophotometry at a wavelength of 411nm.
[0065] The results showed that at a temperature of 25°C, the solubility of ferric maltol-oxalic acid eutectic in water was 5.40 mg / mL, which is lower than the solubility of ferric maltol crystals (9.03 mg / mL). For the easily soluble ferric maltol, from the perspective of formulation, the low-solubility ferric maltol-oxalic acid eutectic has some unique advantages, especially in the design and development of sustained-release drug formulations. The advantages of low solubility are more obvious. Low-solubility eutectics usually dissolve slowly. This property can be used to design long-acting drug release systems to ensure that the drug is released more steadily and persistently in the body, avoiding peak drug concentrations in a short period of time.
[0066] Comparative Example 1
[0067] Screening and Preparation of Cocrystal of Ferric Maltol and L-Cysteine
[0068] According to Table 3, maltol iron and L-cysteine were weighed, 0.5 mL of organic solvent was added, and the mixture was slurried with magnetic stirring at room temperature (25°C) for 6 days, filtered, and the filter cake was vacuum dried at 40°C for 24 hours. The product was characterized by an X-ray powder diffraction (PXRD) instrument, using Cu-Kα radiation, and its PXRD pattern is shown in the figure Figure 7 As shown. Figure 7 It can be seen that the characteristic diffraction peaks of the obtained product are basically consistent with those of ferrous maltol and L-cysteine, that is, ferrous maltol and L-cysteine cannot form a eutectic.
[0069] Table 3. Conditions for preparing cocrystals of ferric maltol and L-cysteine
[0070] Serial number Maltol iron / mg L-cysteine / mg Molar Ratio Organic solvents Stirring time 1 20 5.62 1:1 acetone 6 days 2 20 5.62 1:1 Ethanol 6 days 3 20 5.62 1:1 Acetonitrile 6 days 4 20 5.62 1:1 Ethyl acetate 6 days
[0071] Comparative Example 2
[0072] Screening and preparation of maltol iron and nicotinamide cocrystal
[0073] According to Table 4, the specified mass of maltol iron and nicotinamide were weighed, 0.5 mL of organic solvent was added, and the mixture was slurried with magnetic stirring at room temperature (25°C) for 6 days, filtered, and the filter cake was vacuum dried at 40°C for 24 hours. The product was characterized by an X-ray powder diffraction (PXRD) instrument, using Cu-Kα radiation, and its PXRD pattern is shown in the figure Figure 8 As shown. Figure 8It can be seen that the characteristic diffraction peaks of the obtained product are basically consistent with those of ferrous maltol and nicotinamide, that is, ferrous maltol and nicotinamide cannot form a eutectic.
[0074] Table 4. Conditions for preparing co-crystals of maltol iron and nicotinamide
[0075] Serial number Maltol iron / mg Nicotinamide / mg Molar Ratio Organic solvents Stirring time 1 20mg 5.67mg 1:1 acetone 6 days 2 20mg 5.67mg 1:1 Ethanol 6 days 3 20mg 5.67mg 1:1 Acetonitrile 6 days 4 20mg 5.67mg 1:1 Ethyl acetate 6 days
Claims
1. A maltol iron-oxalic acid eutectic, characterized in that: The eutectic is formed by using maltol iron as the active ingredient and oxalic acid as the eutectic ligand through a suspension stirring method.
2. The maltol iron-oxalic acid eutectic according to claim 1, characterized in that: In the X-ray powder diffraction pattern measured using Cu-Kα radiation, the maltol iron-oxalic acid cocrystal has characteristic diffraction peaks at diffraction angles 2θ of approximately 14.7±0.2°, 17.0±0.2°, 17.6±0.2°, 24.8±0.2°, 26.6±0.2°, and 26.9±0.2°.
3. The method according to claim 1 or 2 is characterized in that: In the X-ray powder diffraction pattern measured using Cu-Kα radiation, the maltol iron-oxalic acid cocrystal has characteristic diffraction peaks at diffraction angles 2θ of approximately 14.7±0.2°, 15.9±0.2°, 17.0±0.2°, 17.6±0.2°, 22.0±0.2°, 24.8±0.2°, 25.7±0.2°, 26.6±0.2°, and 26.9±0.2°.
4. According to claim 1, maltol iron-oxalic acid eutectic, characterized in that: The ferric maltol-oxalic acid eutectic has an X-ray powder diffraction pattern as shown in FIG. 1 or FIG. 5 .
5. The ferric maltol-oxalic acid eutectic according to claim 1, characterized in that: The infrared absorption spectrum of the maltol iron-oxalic acid eutectic is at 1074.41 cm -1 、1205.56cm -1 、1277.91cm -1 、1353.16cm -1 、1384.55cm -1 、1399.84cm -1 、1495.65cm -1 、1560.58cm -1 、1606.82cm -1 、1664.18cm -1 、3256.93cm -1 There is a characteristic peak near it; in the differential scanning calorimetry spectrum, the maltol iron-oxalic acid eutectic has a single endothermic melting peak at 310.93℃.
6. A method for preparing the ferric maltol-oxalic acid eutectic according to claim 1, characterized in that: include: The method comprises adding maltol iron and oxalic acid into an organic solvent, stirring for reaction, filtering, and vacuum drying to obtain maltol iron-oxalic acid eutectic; wherein the organic solvent is ethanol, methanol, acetonitrile, ethyl acetate or a mixed solvent of at least two of the above organic solvents, preferably ethanol.
7. The method for preparing the ferric maltol-oxalic acid eutectic according to claim 6, characterized in that: The molar ratio of the maltol iron to oxalic acid is 1:1 to 1:2, preferably 1:
1.
8. The method for preparing the ferric maltol-oxalic acid eutectic according to claim 6, characterized in that: The dosage ratio of the ferric maltol to the organic solvent is 2:1 to 500:1 mg / mL, preferably 50:1 to 200:1 mg / mL.
9. The method for preparing the ferric maltol-oxalic acid eutectic according to claim 6, characterized in that: The reaction temperature is 25-45°C, preferably 15-30°C; the reaction time is 3-7 days, preferably 5-6 days.
10. A pharmaceutical composition, characterized in that: It comprises the maltol iron-oxalic acid eutectic according to claim 1, and a pharmaceutically acceptable carrier.
Citation Information
Patent Citations
Novel polymorphic form of ferric maltol
US20210139518A1
Crystalline forms of ferric maltol
WO2016066555A1
Crystalline forms of ferric maltol
CN107001310A
Preparation method of maltol iron crystal form II
CN112574158A
Preparation method of iron maltol crystal form V
CN118206519A